Genotype–phenotype correlation in seven motor neuron disease families with novel ALS2 mutations. Issue 2 (5th November 2020) - Sprute, Rosanne; Jergas, Hannah; Ölmez, Akgün; Alawbathani, Salem; Karasoy, Hatice; Dafsari, Hormos Salimi; Becker, Kerstin; Daimagüler, Hülya‐Sevcan; Nürnberg, Peter; Muntoni, Francesco; Topaloglu, Haluk; Uyanik, Gökhan; et al.
Abstract: Autosomal‐recessive mutations in the Alsin Rho guanine nucleotide exchange factor (ALS2) gene may cause specific subtypes of childhood‐onset progressive neurodegenerative motor neuron diseases (MND). These diseases can manifest with a clinical continuum from infantile ascending hereditary spastic paraplegia (IAHSP) to juvenile‐onset forms with or without lower motor neuron involvement, the juvenile primary lateral sclerosis (JPLS) and the juvenile amyotrophic lateral sclerosis (JALS). We report 11 patients from seven unrelated Turkish and Yemeni families with clinical signs of IAHSP or JPLS. We performed haplotype analysis or next‐generation panel sequencing followed by Sanger Sequencing to unravel the genetic disease cause. We described their clinical phenotype and analyzed the pathogenicity of the detected variants with bioinformatics tools. We further reviewed all previously reported cases with ALS2 ‐related MND. We identified five novel homozygous pathogenic variants in ALS2 at various positions: c.275_276delAT (p.Tyr92CysfsTer11), c.1044C>G (p.Tyr348Ter), c.1718C>A (p.Ala573Glu), c.3161T>C (p.Leu1054Pro), and c.1471+1G>A (NM_020919.3, NP_065970.2). In our cohort, disease onset was in infancy or early childhood with rapid onset of motor neuron signs. Muscle weakness, spasticity, severe dysarthria, dysphagia, and facial weakness were common features in the first decade of life. Frameshift and nonsense mutations clustered in the N‐terminal Alsin domains are most prevalent. We enriched the mutational spectrum of ALS2 ‐related disorders with five novel pathogenic variants. Our study indicates a high detection rate of ALS2 mutations in patients with a clinically well‐characterized early onset MND. Intrafamilial and even interfamilial diversity in patients with identical pathogenic variants suggest yet unknown modifiers for phenotypic expression.